The trouble with representation: landscape and environmental justice. (18th May 2016) - Mels, Tom
Abstract: In landscape studies, at the turn of the twenty-first century, the concept of representation has been high on the agenda. Representation has often been understood as the expression of particular cultural politics of landscape, accentuating the socially biased and incomplete nature of textual and visual mediations of the world. In more recent work, it is possible to discern a shift from this emphasis on cultural representation to a fuller engagement with political representation. The concern here, crucially, is to understand representation as a core concept of justice, entwined with the social and material struggle over the right to landscape. In effect, to understand how landscapes materialise struggles over justice, an engagement with political representation is indispensable. As this paper elucidates, one potential consequence of the rediscovery of the political logic of representation is a rapprochement of landscape studies with environmental justice.